The Decoration of ZnO Nanoparticles by Gamma Aminobutyric Acid, Curcumin Derivative and Silver Nanoparticles: Synthesis, Characterization and Antibacterial Evaluation - Chanon Talodthaisong; Kittiya Plaeyao; Chatariga Mongseetong; Wissuta Boonta; Oranee Srichaiyapol; Rina Patramanon; Navaphun Kayunkid; Sirinan Kulchat (Nanomaterials, 2021)
Zinc oxide nanoparticles (ZnO NPs) are applied in various applications in catalysis, biosensing, imaging, and as antibacterial agents. Here we prepared ZnO nanomaterials decorated by γ-aminobutyric acid (GABA), curcumin derivatives (CurBF2) and silver nanoparticles (CurBF2-AgNPs). The structures of all ZnO nanostructures were characterized using Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), UV–VIS spectrophotometry, fluorescence spectrophotometry, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and high-resolution transmission electron microscopy (HR-TEM). Further, their antibacterial activities against Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus) bacteria were investigated through analysis of minimum inhibitory concentration (MIC) method. Among the prepared nanostructures, the ZnO NPs-GABA/CurBF2-AgNPs showed excellent antibacterial activity against both Gram-positive and Gram-negative bacteria. ZnO NPs fabricated here may have potential use in future anti-bacterial compositions and coatings technologies.